Comparison of Mortality and Morbidity of Robotic Versus Laparoscopic Radical Nephrectomy for the Treatment of Renal Cell Carcinoma—An Analysis of the National Surgery Quality Improvement Program (NSQIP) Targeted Nephrectomy Database - Vatsala Mundra; Siqi Hu; Renil Sinu Titus; Eusebio Luna-Velazquez; Zachary Melchiode; Jiaqiong Xu; Carlos Riveros; Sanjana Ranganathan; Emily Huang; Brian J. Miles; Dharam Kaushik; Christopher J. D. Wallis; et al. (Current Oncology)
Objectives: To compare the perioperative complications between robot-assisted (RARN) and laparoscopic (LRN) radical nephrectomy for the treatment of renal cell carcinoma (RCC). Methods: We conducted a retrospective study using the National Surgical Quality Improvement Program (NSQIP) Nephrectomy-Targeted database from 2019 to 2021. After using propensity score matching, we assessed the association between LRN vs. RARN and the outcomes of interest (primary outcomes of 30-day mortality, return to the operating room, myocardial infarction, and stroke; and secondary outcomes of perioperative complications and nephrectomy-specific outcomes). Results: Among the 1545 patients in the study (mean age: 62.9 ± 11.8 years), 722 underwent RARN and 823 underwent LRN. We did not observe any differences in the major complications between the two approaches. However, LRN was associated with an increased chance of surgical site infections compared with RARN (LRN 2.68% vs. RARN 1.19%, p = 0.047). LRN was also associated with a higher likelihood of a prolonged length of stay (OR 1.54, 95% CI: 1.15, 2.06, p = 0.004) and had a 2.7 times higher chance of conversion rate to open surgery (OR 3.70, 95% CI: 3.25, 4.15, p < 0.001) relative to RARN. However, RARN was associated with a longer operative time than LRN (estimated coefficient 30.67, p < 0.001). Conclusion: We found no significant difference in the major complications between RARN and LRN for patients undergoing radical nephrectomy. At the expense of a somewhat longer operative time, RARN was associated with a lower risk of SSI and a lower conversion rate to open RN. LRN and RARN should both be considered and selected on an individualized basis using tumor, patient, and physician factors.